Parents' desire to make equal inter vivos transfers - Elin Halvorsen; Thor Olav Thoresen (Center for Economic Studies and ifo Institute (CESifo), 2008)
This study argues that parents have a desire for dividing equally between their children, and that this motive applies to transfers of gifts inter vivos. We suggest that the equal division motive competes with traditional altruism: support to the child or the children with greatest needs. When parents are drawn between these two ambitions, the degree of income compensation should be stronger in one-child families and we expect the altruism motive to dominate the equal division desire at low levels of recipients' income. We find support for both these hypotheses, when analysing Norwegian data for inter vivos transfers behaviour. The data include information about stated attitudes towards transfers among the parents, which also support the equal division motive.
Keywords: D64; D91; H21; 330; Inter vivos gifts; equal divisions altruism; sibling comparisons; Geschenk; Eltern; Kinder; Altruismus; Gerechtigkeit; Schätzung; Norwegen